2023
DOI: 10.3390/ijms242417489
|View full text |Cite
|
Sign up to set email alerts
|

Phenotype–Genotype Correlations in Three Different Cases of Adult-Onset Genetic Focal Segmental Glomerulosclerosis

Tibor Kalmár,
Sándor Turkevi-Nagy,
László Bitó
et al.

Abstract: This study highlights the importance of a combined diagnostic approach in the diagnosis of rare diseases, such as adult-onset genetic FSGS. We present three adult patient cases evaluated with kidney biopsy for proteinuria, chronic kidney disease, and hypertension, which were suggestive of adult-onset genetic FSGS. Renal biopsy samples and formalin-fixed, paraffin-embedded fetal kidneys were evaluated using standard light microscopical stainings, direct immunofluorescence on cryostat sections, and electron micr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Literatures have reported that some individuals with AS are associated with a phenotype of hypertension. 23 We aimed to investigate whether a genotype-phenotype correlation exists within this large family. However, we only observed hypertension in patient IV-2 (230/140mmHg), while no such phenotype was present in the other family members.…”
Section: Discussionmentioning
confidence: 99%
“…Literatures have reported that some individuals with AS are associated with a phenotype of hypertension. 23 We aimed to investigate whether a genotype-phenotype correlation exists within this large family. However, we only observed hypertension in patient IV-2 (230/140mmHg), while no such phenotype was present in the other family members.…”
Section: Discussionmentioning
confidence: 99%